Intervención del terapista respiratorio en paciente masculino de 9 años de edad con asma bronquial. - Villalva Terán, Rosa Belén (2023)
Asthma is a lung disease that causes inflammation and narrowing of the airways, which in turn makes breathing difficult. The main signs and symptoms of this disease are wheezing, coughing and chest tightness. The main causal agents of bronchial asthma in the 9-year-old male patient were that the patient is exposed to dust, cigarette smoke because he lives with a relative who is an active smoker, he is also exposed to chemical odors because a few meters from his home there is a banana plantation and all these agents are considered risk factors for the development of bronchial asthma. The clinical case is based on the intervention of the respiratory therapist in a 9-year-old male patient with a diagnosis of bronchial asthma who presents a clinical picture characterized by oppressive chest pain, respiratory distress, cough with expectoration of 24 hours of evolution, which becomes more acute at night, tiredness when walking and wheezing. The correct treatment of patients with this disease depends on the clinical exacerbation, so all patients with this disease should apply the appropriate treatment and care according to the severity